ANALISIS KESALAHAN SISWA KELAS VII-B SMP MARGA UTAMA PADALARANG PADA PENYELESAIAN SOAL MATERI ALJABAR BERDASARKAN INDIKATOR TAKSONOMI BLOOM DAN GENDER - Hasan Sidik; Risma Amelia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze student errors in solving math problems in algebraic material. The algebra questions tested have been compiled based on Bloom's taxonomy. The indicators in each question contain various abilities that exist in Bloom's taxonomy, such as the ability to calculate, relate, conceptualize, investigate and others. The method used in this research is descriptive qualitative research. The subjects of this study were students of class VII-B SMP Marga Utama Padalarang. Many samples in this study were 20 students consisting of 10 male students and 10 female students. The items tested are 5 items with the type of essay questions. Based on the results of data analysis in the form of a test consisting of 5 algebraic essay questions, it shows that there are differences in the errors made by male students and female students. The most errors in solving algebra questions were made by male students, as many as 70%. The error is because students are accustomed to practice questions given by teachers not using Bloom's taxonomy when designing the questions. In other words, students are only used to the same questions as the example questions explained by the teacher before. As a result, students find it difficult when solving algebra problems that have been designed using Bloom's taxonomy and end up making many mistakes when answering the questions.